Alternative Utilization of Photovoltaic Panels from the Solar Home System Project for Rural Community - ปานประยูร, ดร.กันต์ (Journal of Food Health and Bioenvironmental Science, 2017)
The concept of this research was to find out sustainable solutions for the Solar Home System (SHS) project; especially for abandoned systems due to malfunction of system components including battery, charge controller, inverter, and even access to the grid utility. However, photovoltaic panels are able to be applied for alternative utilizations. The results of the Solar Home System (SHS) potential evaluation showed that 93.5% of photovoltaic panels, were working normally. The photovoltaic panels could be applied to generate electricity for remote learning or community health facilities. The alternative systems include a stand-alone system with a battery or a PV-diesel engine hybrid system for tasks that need more reliability and a grid-connected system in case of grid utility access. The designed system produced 5.6 kWp that could support an electricity demand of about 20 kWh per day. The costs of energy were about 11.32, 7.05, 1.36 Baht/kWh, respectively.